Human biomonitoring in health risk assessment in Europe: current practices and recommendations for the future - Louro, Henriqueta (2019)
Human biomonitoring (HBM) is an important tool to survey the internal exposure of humans which represents the real-life chemical body burden to chemicals and/or their metabolites. It results from total exposure to chemical substances from different sources and via different routes. These substances may be regulated under different legislative frameworks on chemicals (e.g., environmental, occupational, food safety, etc). In occupational health, HBM has long traditions to control the exposures at workplaces. By providing accurate data on internal exposure, HBM data can improve human health risk assessment (RA) for both the general population and workers. Although the past few years have shown good examples of the use of HBM in the RA of chemicals, there is still quite some work to be done to improve its use in a regulatory RA. Under the scope of the European Human Biomonitoring Initiative (project HBM4EU, 2017-2021), the current study reviews the state-of-the-art of HBM use in chemicals RA with a special focus in Europe and attempts to identify hurdles and challenges faced by regulators. To gather information on the use of HBM, including the availability of guidance on how to use it in RA, the RA schemes applied by different European or international organizations were analyzed. Examples of such use were identified for a few selected groups of chemicals of concern for human health. In addition, we present the results of a survey, aimed at collecting information from national regulatory risk assessors on their day-to-day RA practices, the use of HBM data, and the obstacles and challenges related to their use. The results evidenced and explained some of the current obstacles of using HBM data in RA. These included the lack of HBM guidance values or biomonitoring equivalents (BEs), limited toxicokinetic information to support the interpretation of HBM data and, in the occupational health and safety (OSH) field, the lack of legal enforcement. Therefore, to support the integration of HBM in regulatory RA, we recommend, on one hand, the elaboration of an EU level guidance on the use of HBM in RA and, on the other hand, the continuation of research efforts to integrate HBM with new RA approaches using in vitro/in silico data and Adverse Outcome Pathways (AOPs).